Upaya Optimalisasi Kesesuaian Lahan Budidaya Jamur pada Media Cocopeat berbasis Pengabdian pada Masyarakat di Desar Sumber Urip Provinsi Bengkulu - Faiz Barchia; Heru Widyono; Elsa Lolita Putri (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
This service activity to optimize the suitability of mushroom cultivation land on cocopeat media was carried out in the community in Sumber Urip, Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province. This community service activity aims to provide knowledge and practice of oyster mushroom cultivation on cocopeat media to optimize land suitability and improve the economy of the community, especially those in Sumber Urip. This service is carried out by the method of providing material related to mushroom cultivation on cocopeat media in the form of discussions and questions and answers as well as the practice of oyster mushroom cultivation procedures at the inoculation stage in the community of Sumber Urip Village. The tools and materials used in this service have been provided previously from the community service team. in collaboration with the Dangau Datuk Agribusiness Vocational School, Bengkulu City, namely baglog, seeds, masks, alcohol, spatulas, spirit, and rubber bands. The results obtained from this activity are an increase in the knowledge and interest of the people of Sumber Urip Atas in mushroom cultivation with cocopeat media and it is hoped that the enthusiasm of the community to continue this cultivation to produce quality oyster mushrooms and continue to other types of household businesses..